A estética vocal de cantoras paraibanas: Marinês, Cátia de França e Elba Ramalho. - Figueirêdo, Anne Raelly Pereira de (2010)
This paper presents the research results who try to comprehend fundamental definitions aspects of vocal esthetics in musical expressions of Paraíba´s female singers, specifically focused at three state musicians with local, regional and national recognition, they are: Marinês, Elba Ramalho and Cátia de França. This work was based with views of ethnomusicology and related fields. The methodological research evolved bibliographical research, record, sound, documental research, participative observation and half-structured interviews, as well data analysis and organization resources which could generate a clear, wide and contextualized view of the researched reality. Based on the research realized, the discussions and analysis done throw the paper became evident that the vocal esthetics of each singer was defined by the inter-relation of multiple aspects linked to physiological dimensions and voice techniques, to the use of recording technological resources, voice effects and amplifications and to cultural background in general that point the history of each female singer studied.